The atomic bomb : voices from Hiroshima and Nagasaki - Kyoko and Selden, Mark, editor (London and New York : M. E Sharpe, 1989)
This collection of factual reports, short stories, poems and drawings expresses in a deeply personal voice the devastating effects of the bombings of Hiroshima and Nagasaki.
Keywords: Bombardament; Hiroshima; Atomic bomb victims -- Japan; World War, 1939-1945 -- Personal narratives, Japanese; Hiroshima-shi (Japan) -- History -- Bombardment, 1945